Implementasi Hukum Adat dalam Pembagian dan Penyelesaian Sengketa Waris pada Masyarakat Minangkabau: Studi Kasus Kerapatan Adat Pagaruyung - Ismatul Karimah; Ade Gunawan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Indonesia also recognizes customary inheritance law that encompasses a variety of different traditions and legal systems, depending on the ethnic group and region. Referring to inheritance law in Minangkabau, the indigenous community is known for its matrilineal kinship system, where lineage and inheritance are inherited through the mother's lineage. This study aims to determine the implementation of the distribution of customary inheritance law in Minangkabau indigenous peoples. This research uses the Normative-Empirical method, because the researcher combines elements of normative and empirical law, and the author also examines a legal case from an interview with the Chairman of the Nagari Pagaruyuang Customary Density. In Minangkabau society, the applicable inheritance law is different from inheritance law in civil law, the kinship system adopted is a matrilineal kinship system with the distribution of inheritance in the form of sako and pusako. Dispute resolution involves the active role of the customary clan/elder as mediator, decision-maker, and implementation of the decision. Inheritance disputes in Minangkabau society are a complex phenomenon involving various cultural, social and legal factors. Minangkabau customary law plays a central role in regulating inheritance distribution and conflict resolution. Values such as kinship, social justice and deliberation are key principles in this process, with deliberation as a means to reach mutual agreement in dispute resolution.